Black-pigmented anaerobic bacteria associated with ovine periodontitis - Borsanelli, Ana C. [UNESP]; Gaetti-Jardim, Elerson [UNESP]; Schweitzer, Christiane M. [UNESP]; Viora, Lorenzo; Busin, Valentina; Riggio, Marcello P.; Dutra, Iveraldo S. [UNESP] (Elsevier B.V., 2017)
Periodontitis is a polymicrobial infectious disease that causes occlusion change, tooth loss, difficulty in rumination, and premature culling of animals. This study aimed to detect species of the genera Porphyromonas and Prevotella present in the periodontal pocket of sheep with lesions deeper than 5 mm (n = 14) and in the gingival sulcus of animals considered periodontally healthy (n = 20). The presence of microorganisms was evaluated by polymerase chain reaction (PCR) using specific primers for Porphyromonas asaccharolytica, Porphyromonas endodontalis, Porphyromonas gingivalis, Porphyromonas gulae, Prevotella buccae, Prevotella intermedia, Prevotella loescheii, Prevotella melaninogenica, Prevotella nigrescens, Prevotella oralis, and Prevotella tannerae. Prevalence and risk analysis were performed using Student's t-test and Spearman's correlation. Among the Prevotella and Porphyromonas species detected in the periodontal lesions of sheep, P. melaninogenica (85.7%), P. buccae (64.3%), P. gingivalis (50%), and P. endodontalis (50%) were most prevalent. P. gingivalis (15%) and P. oralis (10%) prevailed in the gingival sulcus. P. gulae and P. tannerae were not detected in the 34 samples studied. Data evaluation by t-test verified that occurrence of P. asaccharolytica, P. endodontalis, P. gingivalis, P. buccae, P. intermedia, P. melcdinogenica, and P. nigrescens correlated with sheep periodontitis. The findings of this study will be an important contribution to research on pathogenesis of sheep periodontitis and development of its control measures.
Keywords: Periodontal disease; Periodontitis; Sheep; Prevotella; Porphyromonas